Historical Overview of the Traditional Ghanaian Seats - Appiah-Kubi, Obed Persie; Inkum, Paul Benedict; Owusu-Ansah, Phoebe Prisca; Akomeah, Ronit; Agyakwa, Emmanuel Amisare; Wu, Zhihui; Feng, Xinhao (International Journal of Culture and History, 2024)
Traditional Ghanaian seats have existed for centuries. As of now, there is no complete research material detailing its history, nature, types, functions, appropriate materials for production, and the symbolic designs conveyed in the craft making it incomplete to tell the rich culture of Ghana. The paper aims at providing a more detailed overview of the craft to serve as complete and reliable reference material to learners. This qualitative study employed the narrative research design. The study was conducted at Ahwiaa and Bomani Tyehimba traditional wood carving communities in the Ashanti and Eastern regions of Ghana respectively. Two historians; one each, and ten traditional stool carvers; five each from the visited carving communities were purposively selected and interviewed. The craft was initiated by the Ashantis and traveled to other regions. The craft has a flat rectangular base, a center section, and a crescent-shaped top. The center section contains distinctive motifs and symbolic meanings that are the source of the numerous stools’ names. Some symbolic wisdom conveyed in the craft includes; Gye Nyame, Bi nka bi, Akofena, Sankofa, etc. Ahemmaa dwa, Mmarima dwa, Mmaa dwa, Osram dwa, Kotoko dwa, Esono dwa, etc. are some common types of the craft. It functions as practical items in every home, as a connection to rites of passage, as religious artifacts, and as a political allegory. Wood like Osese (Funtumia sp.), Nyame dua (Alstonia gongensis), Cedrela (Cedrela odorata), Mahogany (Swietenia mahagoni), teak (Tectona grandis), etc. are used for the production. The study will add up to the Ghanaian citizens, foreigners, and researchers’ knowledge to know much about the craft and the cultural heritage of the country.